The Urgency of Environmental Education in Shaping Pro-Environmental Behavior Among Gen Z University Students - Arbiana Putri (CV. Edujavare Publishing, 2025)
Environmental education plays a strategic role in shaping pro-environmental behavior, particularly among Generation Z university students who have grown up amidst rapid digital technological advancements and heightened awareness of sustainability issues. This study aims to describe the role of environmental education specifically within the